Evaluation of Electrical Installation Training Conducted by the Employment Training Center of Pandeglang Regency, Banten, Indonesia - Triani Wahyuningsih; Ilham Akbar Darmawan; Mustofa Abi Hamid (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
This research aimed to explore the results of the evaluation of Electrical Installation Training of the Technical Support Unit of Employment Training Center of Pandeglang Regency based on aspects including context, input, process, product, and outcome, so that recommendation can be obtained for the next training.  This study employed a qualitative descriptive method. The CIPPO evaluation model was used in this study. The results indicated that while the setting, process, and product elements could be classified as satisfactory, the input and outcome aspects remained in the poor category. Nonetheless, even with remaining limitations in terms of input and implementation outcomes, the training program can run well. This electrical installation training can be extended by strengthening program components on the input side, particularly facilities and infrastructure, as well as on the output side, in order to maximize labor absorption and reduce unemployment.